Ilmu Pendidikan Islam Versi Perspektif Nasional dan Lembaga Pendidikan - Munir Munir (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2017)
Education is an elementary element that can not be separated from the theological aspect. Theological Islamic commitment to education can be traced to the Qur'an of al-Alaq (96): 1-14. The verses in this letter describe the significance of true knowledge that must be known and spread by Muslims in particular and mankind in general. Abdullah Yusuf Ali explains that the phrase